The Changes of Viability, Vigor, and Biochemical Content of Trema (Trema orientalis Linn. Blume) Seeds during Storage - Naning Yuniarti; Dida Syamsuwida; Rina Kurniaty (Foresty Faculty of Hasanuddin University, 2018)
The seed of trema (Trema orientalis Linn. Blume) is categorized as physiologically intermediate which decline faster during storage compared to orthodox seeds, resulting in the changes of its viability, vigor and biochemical contents.The study was objected to determine the changes of viability, vigor and biochemical contents of trema seeds during storage. The seeds were collected from Badung - Bali province. Seeds testing were carried out in a laboratory and glasshouse of Forest Tree Seed Technology Research & Development Centre. Biochemical analysis was implemented in Soil and Plant Laboratory, Seameo[1]Biotrop. A Completely Randomized Design was employed in this trial with a treatment of storage periods (0.1, 2, 3, 4, 5 and 6 months). The parameters were germination capacity, germination speed, moisture content and biochemical content including carbohydrate, protein and fat. The results revealed that all the parameters were significantly affected by storage periods. After six months periods of trema seeds storage, it would caused the decrease of moisture content (6.2%), germination capacity (61%), germination speed (2.5%/etmal), carbohydrate (19.2%) and protein contents (1.8%). However, the content of fat was increased significantly (10.2%).